Population modelling to compare chronic external radiotoxicity between individual and population endpoints in four taxonomic groups. (February 2016) - Alonzo, Frédéric; Hertel-Aas, Turid; Real, Almudena; Lance, Emilie; Garcia-Sanchez, Laurent; Bradshaw, Clare; Vives i Batlle, Jordi; Oughton, Deborah H.; Garnier-Laplace, Jacqueline
Abstract: In this study, we modelled population responses to chronic external gamma radiation in 12 laboratory species (including aquatic and soil invertebrates, fish and terrestrial mammals). Our aim was to compare radiosensitivity between individual and population endpoints and to examine how internationally proposed benchmarks for environmental radioprotection protected species against various risks at the population level. To do so, we used population matrix models, combining life history and chronic radiotoxicity data (derived from laboratory experiments and described in the literature and the FREDERICA database) to simulate changes in population endpoints (net reproductive rate R 0, asymptotic population growth rate λ, equilibrium population size N eq ) for a range of dose rates. Elasticity analyses of models showed that population responses differed depending on the affected individual endpoint (juvenile or adult survival, delay in maturity or reduction in fecundity), the considered population endpoint ( R 0, λ or N eq ) and the life history of the studied species. Among population endpoints, net reproductive rate R 0 showed the lowest EDR 10 (effective dose rate inducing 10% effect) in all species, with values ranging from 26 μGy h −1 in the mouse Mus musculus to 38, 000 μGy h −1 in the fish Oryzias latipes . For several species, EDR 10 for population endpoints were lower than the lowest EDR 10 for individual endpoints. Various population level risks, differing in severity for the population, were investigated. Population extinction (predicted when radiation effects caused population growth rate λ to decrease below 1, indicating that no population growth in the long term) was predicted for dose rates ranging from 2700 μGy h −1 in fish to 12, 000 μGy h −1 in soil invertebrates. A milder risk, that population growth rate λ will be reduced by 10% of the reduction causing extinction, was predicted for dose rates ranging from 24 μGy h −1 in mammals to 1800 μGy h −1 in soil invertebrates. These predictions suggested that proposed reference benchmarks from the literature for different taxonomic groups protected all simulated species against population extinction. A generic reference benchmark of 10 μGy h −1 protected all simulated species against 10% of the effect causing population extinction. Finally, a risk of pseudo-extinction was predicted from 2.0 μGy h −1 in mammals to 970 μGy h −1 in soil invertebrates, representing a slight but statistically significant population decline, the importance of which remains to be evaluated in natural settings. Highlights: We simulated population effects of chronic radiation in 12 species and 4 taxonomic groups. Radiotoxicity and life history data from the literature were used to build matrix population models. Population response varied among affected individual endpoints and species life histories. Population endpoints can be more radiosensitive than the most sensitive individual endpoint. Reference benchmarks from the literature were assessed for a range of population risks.